Analisis Respon Time Perawat dengan Complaint Handling dalam Pelayanan Keperawatan di Instalasi Gawat Darurat Primaya Hospital Tangerang - Nawangwulan, Rahayu; Hasanah, Uswatun; Puspita, Ratumas Ratih; Wisnu Wardani, Dita Sri Sri Ayu (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2023)
Hospitals are required to provide quality services in accordance with established standards and can reach all levels of society. The increasing demands of the community for health facilities, especially in hospitals, continuously make hospitals have to make efforts to improve the quality of health service delivery, including improving the quality of nursing services. The nurse's response time is one of the process indicators that is assessed from the time the patient enters the emergency room to achieve an outcome indicator, namely patient survival. The right response time will give the patient confidence in the hospital, and will feel satisfied with the hospital's services and prevent complaints from occurring. The purpose of this study was to determine the relationship between nurse response time and complaint handling in nursing services at emergency room Primaya Hospital Tangerang. The research method used is a quantitative research design with a correlational study. The results of the analysis showed that there was a significant relationship between nurse response time and complaint handling in nursing services at the Primaya Hospital Tangerang emergency room based on the results of the chi-square statistical test with p value = 0.027 (p 0.05). The conclusion obtained in this study is that there is a relationship between nurse response time and complaint handling in nursing services at the IGD Primaya Hospital Tangerang. Suggestions from the results of this study are that nurses can provide appropriate services to patients according to the predetermined response time to prevent complaints from patients. AbstrakRumah sakit dituntut untuk memberikan pelayanan yang bermutu sesuai dengan standar yang ditetapkan dan dapat menjangkau seluruh lapisan masyarakat. Meningkatnya tuntutan masyarakat di sarana kesehatan terutama di rumah sakit, secara berkesinambungan membuat rumah sakit harus melakukan upaya peningkatan mutu pemberian pelayanan kesehatan, termasuk meningkatkan kualitas pelayanan keperawatan. Respon Time perawat merupakan salah satu indikator proses yang dinilai sejak awal pasien masuk ke IGD untuk mencapai indikator hasil yaitu kelangsungan hidup pasien. Respon time yang tepat akan memberikan kepercayaan pasien terhadap rumah sakit, dan akan merasa puas terhadap layanan rumah sakit dan mencegah terjadinya komplain. Tujuan Penelitian untuk mengetahui hubungan respon time perawat dengan complaint handling dalam pelayanan keperawatan di IGD Primaya Hospital Tangerang. Metode penelitian menggunakan desain penelitian kuantitatif dengan studi korelasional.Populasi adalah pasien di IGD primaya Hospital berjumlah 125 pasien. Sampel berjumlah 95 responden Hasil analisis menunjukan terdapat hubungan antara response time perawat dengan Complaint Handling (Penanganan Keluhan) dalam pelayanan keperawatan di IGD Primaya Hospital Tangerang yang sangat signifikan berdasarkan hasil uji statistik chi-square dengan nilai p=0,027 (p0,05). Kesimpulan terdapat hubungan antara response time perawat dengan Complaint Handling (Penanganan Keluhan) dalam pelayanan keperawatan di IGD Primaya Hospital Tangerang.